From Reception to Intervention: The Oneness of God in the Torah, the Bible, and the Qur’an - Abdul Qawwiy Nasrun; Alya Firdausi Emha; Zukhrifa 'Amilatun Sholiha (UIN Sunan Kalijaga Yogyakarta, 2025)
This article examines the concept of the oneness of God through an intertextual analysis of three scriptures: the Torah, the Bible, and the Qur’an. In the Torah, God is YHWH, the sole sovereign who rules over heaven and earth. Similarly, the Bible contains the doctrine of divine oneness, albeit with a “modification” of YHWH into the concept of Trinitarian monotheism. The Qur’an, meanwhile, presents the doctrine of God’s absolute oneness (aḥad). The primary sources of this study are the original texts and translations of the Qur’an, the Bible, and the Torah. Scholarly works on religious studies and intertextuality serve as secondary sources. The study concludes that, with the Qur’an positioned as a new signifying text and the Bible and the Torah as referential signifying systems, there are at least four forms of transposition: parallelism, demythification, modification, and expansion. These intertextual forms demonstrate that the Qur’an frequently intervenes in the dominant discourses of the Torah and the Bible. Accordingly, the Qur’an should be understood as a text of reception history as well as an active intervention within early Islam.